The Effect of InfoBMKG Application Using Toward Disaster Responsiveness Attitude of Mataram University Students Post Lombok Earthquake - Putri Arifatul Fajriyah; Diyah Indiyati; Agus Purbathin Hadi (Universitas Mataram, 2019)
This research was carried out after the Lombok earthquake that occurred repeatedly in July and August 2018. In such situations, people need quick and practical information about the earthquake. One of the ways to get practical and fairly accurate information is using the InfoBMKG application. The application is expected to be able to make people more alert and careful about disasters. This study aims to see the effect of using the BMKG Info application on community disaster response attitudes. The object of this research is Universitas Mataram Students. This study uses a quantitative descriptive method on 100 respondents who use the Info BMKG application. Data analysis was done by categorizing data into high, medium, and low, then correlation test to see the relationship, and regression test to see the effect of the variable use of BMKG Info application on disaster response attitude variables. The results of study indicate that there is a strong relationship between the use of the InfoBMKG application and the responsiveness of Universitas Mataram students, and 15.7% of disaster readiness attitudes of Universitas Mataram students are affected by the use of the InfoBMKG application.Keywords: Lombok earthquake; Info BMKG Application; disaster readiness attitudes